2017
DOI: 10.1371/journal.pone.0185014
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype analysis and sex determination in Australian Brush-turkeys (Alectura lathami)

Abstract: Sexual differentiation across taxa may be due to genetic sex determination (GSD) and/or temperature sex determination (TSD). In many mammals, males are heterogametic (XY); whereas females are homogametic (XX). In most birds, the opposite is the case with females being heterogametic (ZW) and males the homogametic sex (ZZ). Many reptile species lack sex chromosomes, and instead, sexual differentiation is influenced by temperature with specific temperatures promoting males or females varying across species posses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Generally, the genetic system of sex determination for a species could be uncovered through descent identification or karyotype analysis ( Malecha et al, 1992 ; Ortega et al, 2017 ). Presently, high-throughput sequencing has been used as a rapid and efficient way to uncover the sex determination system of an organism ( Pan et al, 2015 ; Ou et al, 2017 ; Shi X. et al, 2018 ; Gao et al, 2019 ; Yang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the genetic system of sex determination for a species could be uncovered through descent identification or karyotype analysis ( Malecha et al, 1992 ; Ortega et al, 2017 ). Presently, high-throughput sequencing has been used as a rapid and efficient way to uncover the sex determination system of an organism ( Pan et al, 2015 ; Ou et al, 2017 ; Shi X. et al, 2018 ; Gao et al, 2019 ; Yang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chickens have a large number of microchromosomes; therefore, it is inconvenient to count and describe the chromosomal morphology. Some studies have demonstrated that the incomplete karyotypes of the first 10 chromosomes in birds can represent a species-specific karyotype [3] .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, this temperaturedependent loss of males does not occur in birds [discussed in [47]] but other temperature-dependent effects may be operative [48]. Interestingly in many bird species, females are heterogametic (ZW) while males are homogametic (ZZ) [discussed in [49]].…”
Section: The Fundamentals Of Biological Sexmentioning
confidence: 99%